A new species of Hohenbuehelia in Nakhon Phanom, northeastern Thailand - Somrithipol, Sayanh; Pinruan, Umpawa; Sommai, Sujinda; Khamsuntorn, Phongsawat; Luangsa-Ard, J. Jennifer (Phytotaxa, 2025)
Hohenbuehelia nakhonphanomensis, collected from wood in a tropical dry dipterocarp forest in Nakhon Phanom Province, northeastern Thailand, is described as a new species, based on its distinctive morphology and phylogeny. The fungus is characterized by a whitish dimidiate pileus, subglobose to obovoid basidiospores, and possession of small thick-walled cystidia without encrusted crystals that are embedded in the hymenium of a lamella beside the large crystal-encrusted projecting from the hymenium (metuloids), together with the Internal Transcribed Spacer (ITS), the Large subunit of the ribosomal DNA (LSU), and Elongation Factor 1-alpha (tef-1) sequences. Comparisons between this fungus to morphologically and phylogenetically related species are also discussed.